Behavioural Dynamics of Health Insurance Adoption: A Consumer Perspective - Dr. N. Ramanjaneyulu; Dr. G Hari Kumar; M Umrez, (Indian Journal of Management and Language (IJML), 2025)
Health insurance plays a critical role in mitigating the financial risks associated with medical expenses. This study investigates consumer behaviour toward health insurance, focusing on demographic influences, key decision-making factors, and relevant theoretical frameworks. In the aftermath of the pandemic, consumer attitudes toward health insurance have undergone a significant transformation. Once viewed as a discretionary expense, health insurance is now regarded as a crucial component of financial planning. As a result, the demand for health insurance has increased year by year. This paper examines the key factors influencing consumer behaviour, including heightened health awareness, financial preparedness, policy flexibility, digital accessibility, and trust in providers. By understanding these shifts, insurers and policymakers can better align their offerings with consumer needs and expectations in a post-pandemic landscape. Ultimately, this study aims to provide insights into the motivations behind health insurance adoption and the evolving priorities of modern consumers.